IMPACT OF MUSIC VIDEOS ON PORNOGRAPHY EXPOSURE AND SEXUAL ABUSE BEHAVIOR AMONG YOUTHS AND ADOLESCENTS IN NIGERIA - Mumud Olabode Ojuolape; Victor Ayodeji Fehintola; Ayodeji Solomon Adegoke; Ernest Ochuko Okpako; Naseem Akorede Raji; Sylvester Ehimare Umanhonlen; Habeeb Omoponle Adewuyi (Annals of the University of Craiova for Journalism, Communication and Management, 2025)
The study examined how exposure to pornography and sexual abuse behavior among young people in Nigeria is affected by music videos. The descriptive research design of survey type was employed for the study. Using the random sampling technique, 1200 young people in Nigeria were selected. With the regression analysis performed, the results demonstrated that young people and adolescents were exposed to a high level of pornographic music videos and that there was a strong correlation between young people and adolescents' exposure to pornography and sexual abuse behavior. Gender differences were found in the exposure to pornographic music videos, and a significant negative correlation between pornographic music videos and sexual abuse behaviour was recorded. The result of this study has clearly shown that music videos played a role in influencing pornography and sexual abuse behaviour; parents and caregivers should, therefore keep an eye on their kids when they watch music videos.